Design and analysis of induction heating system with parallel resonance inverter - (:unkn) unknown (International Journal of Renewable Energy Research, 2020)
In comparison to the conventional heating systems, the induction heating systems have not only higher efficiency but also quite shorter processing time. Depending on their working conditions, they do not dissipate heat to the environment and cause pollution, and this makes them be environmentally friendly. The fact that the system does not allow any case such as explosion, combustion or injury reveals the reliability of this system. Because of the superiorities mentioned above, day by day it is more widely used in the modern industry treatments such as surface hardening, welding, tempering, rolling, heating, and melting. Whereas the induction heating systems with series resonance are designed as single-phase and low-powered in general, the induction heating systems with parallel resonance are used in high-powered and high-frequency three-phase industrial applications. In this study, an induction heating system which has 17 kW power enabling melting of brass material containing 58% copper, and has a frequency of 14,5 kHz, three-phase, voltage sourced, and full-bridged rectifier with parallel resonance inverter is designed. MATLAB simulation of the designed system is performed, and an analysis is carried out with the obtained results. In the operation of the system, a high current of 1132 A is provided on the load during the resonance. Thus, it is provided that the high value of short circuit current circulating in the brass material, which is considered as a load, produces heat in the part, and melts the metal part in a quite short time. © 2020 Institut za Arhitekturu i Urbanizam Srbije.
Keywords: Induction heating; Melting; Metal part; Parallel resonance inverter; Simulink